Assessing the influence of hedonic shopping motives and positive emotion to online impulse buying: The case of UNIQLO Philippines for Filipino millennials and generation z - Prenksamar, Chinny Montejo (Animo Repository, 2022)
The advancement of technology forges buying faster, smarter, and more convenient for consumers, and consequently provides opportunities for impulse buying. Online shopping has accelerated due to COVID-19-triggered lockdowns, and this sudden growth may become perpetual. These trends have put a renewed spotlight on impulse buying and how marketers can trigger those spontaneous purchases that drive sales and profits. To explore this line of research, the study investigates the influence of various Hedonic Shopping Motives namely, Adventure, Idea, and Value Shopping Motives, and Positive Emotion to Online Impulse Buying of fast fashion items from UNIQLO Philippines. Causal-effect and descriptive were used in the study for the research design. Moreover, a non-probability sampling was used given that the probability of the target respondents being selected cannot be calculated. A total of 394 respondents constituted the sample size, consisting of Generation Z and Millennial Filipino individuals residing in cities of Metro Manila. Simple linear regression was utilized to address the research problems and hypotheses formulated. The result of the data analysis revealed that the Hedonic Shopping Motive, Adventure Shopping Motive, Idea Shopping Motive, Value Shopping Motive, and Positive Emotion have a significant influence on Online Impulse Buying with a p-value of less than 0.05. Key recommendations for UNIQLO Philippines include producing fashion pieces that are more unique to the eyes of its consumers, partnering with well-known individuals or brands, conducting research on which financial institution the brand can partner with to provide more promotions to its customers, and upgrading its website and application to seem more interactive with its customers. Also, for other brands in the industry to take into consideration different Hedonic Shopping Motives and Positive Emotion, and for future researchers to limit the scope of their study’s group of respondents.